Lower-body muscular power and exercise tolerance predict susceptibility to enemy fire and cognitive performance during a simulated military task - Hepler, Timothy Caleb (Kansas State University, 2021)
Physical fitness and performance measures are predictive of Special Forces Assessment and Selection and performance during combat-specific tasks. In combat, approximately 50% of casualties are lost to direct-fire engagements, which requires resiliency to fatigue during repeated high-intensity sprints (under combat load) and delivering suppressive fire while under duress. Currently, the US Army does not have a physical fitness test that is predictive of combat survival. This study examined the predictive ability of field-expedient physical fitness/performance tests on a simulated military task (SMT) that mimicked a direct-fire engagement. Healthy subjects (N = 39, age = 25.3 ± 6.8 years) completed upper- and lower-body strength (i.e., handgrip, isometric midthigh clean pull) and power (i.e., seated power throw, standing broad jump) tests and a 3-minute all-out running test to determine critical velocity. Subjects returned to the laboratory to complete a simulated military task (SMT) that consisted of marksmanship with cognitive workload assessment (CWL) and a fire-and-move simulation (16 6-m bounds) while wearing a vest simulating a combat load (25-kg). Susceptibility to enemy fire was modeled on bound duration during the fire-and-move simulation. Stepwise linear regression identified predictors for the tactical combat movement simulation components. Significant regression models were identified for both susceptibility to enemy fire (R² = 0.755, p < 0.001) and cognitive performance (R² = 0.162, p < 0.05). Critical velocity predicted both susceptibility to enemy fire (β = 0.40, p < 0.01) and cognitive performance (β = -0.30, p < 0.05), and standing broad jump predicted susceptibility to enemy fire (β = -7.20, p < 0.001). All variables demonstrated poor relationships with marksmanship accuracy (r = -0.03-0.24, ps > 0.05) and no statistically significant regression model was identified. These data demonstrate the importance of exercise tolerance (i.e., critical velocity) and lower-body power (standing broad jump) in performance during a simulated direct-fire engagement and provide potential targets for interventions to monitor and enhance performance and support soldier resiliency.
Keywords: Marksmanship; Combat survivability; Susceptibility to enemy fire; Cognitive performance; Critical velocity